SHEAR STRENGTH OF CLAY REINFORCED WITH SQUARE AND TRIANGULAR ARRANGEMENT OF GROUP ENCAPSULATED BOTTOM ASH COLUMNS (GEOMATE Journal, 2017)
Soft clay is known to be a problematic soil that consists of low shear strength, low permeabilityand high compressibility where the existing soil on the given site is low with load bearing capacity, and by thatground improvement is required. Granular column methods are being used extensively as ground improvementtechnique for supporting a wide variety of structures and infrastructures. In practice, the bearing capacity on softclay increased by a layer of compacted sand or gravel. Bottom ash as by product of coal burning that has similarproperties to granular material can be applied as one of the stabilizing method to the existing soil. Hence, byusing bottom ash as substitute, the cost of construction can be reduced and make great progress of a growingawareness of the sustainable engineering. This research discusses the results of the improvement in the shearstrength of soft clay after being reinforced with a group of square and triangular encapsulated bottom ashcolumns. The physical and mechanical properties of the materials used such as kaolin and bottom ash weredetermined. The results show that kaolin can be classified ad clayey soil and bottom ash has similarities ofcharacteristic with granular material. A total of 52 unconfined compression tests had been conducted on kaolinspecimens to determine the shear strength. The diameter for specimen is 50 mm and 100 mm in height. Thediameter of bottom ash columns are 10 mm and 16 mm respectively and the height of the column are 60 mm, 80mm and 100 mm. The group columns have been arranged in square and triangular pattern. It can be concludedthat the shear strength parameters were improved based on the different diameter and the height of the column.